About the Accentual Characteristics of the Variety of Serbian Used in the Danube Gorge (Divič) - Lončar Raičević, Aleksandra R. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Based on the field research carried out on the territory of the Danube Gorge in Romania, in the village of Divič we have collected the material which was used in the analysis of the prosodic characteristics of the given variety. The paper presents the accentual system, including the inventory and the distribution of the prosodemes. One of the most prominent features of this variety is the Old-Shtokavian type of accentuation, i.e. the new system of three accents derived from the Old-Shtokavian inventory with two accents.
Keywords: accents; prosody; Romanian Banat; Serbian speech in Romania